If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 2(r + -4) = 7r Reorder the terms: 8 + 2(-4 + r) = 7r 8 + (-4 * 2 + r * 2) = 7r 8 + (-8 + 2r) = 7r Combine like terms: 8 + -8 = 0 0 + 2r = 7r 2r = 7r Solving 2r = 7r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-7r' to each side of the equation. 2r + -7r = 7r + -7r Combine like terms: 2r + -7r = -5r -5r = 7r + -7r Combine like terms: 7r + -7r = 0 -5r = 0 Divide each side by '-5'. r = 0 Simplifying r = 0
| 3(0+5)-6=3(0+3) | | 1x+6+2x=180 | | -4x^2+x-3=-3 | | 3(7+5)-6=3(7+3) | | 3(2+5)-6=3(2+3) | | y=3*-1-4 | | 5+x=3-2 | | 3n+9=n+30 | | 10(x+5)+66=-17-17 | | x+(10x)=132 | | 9x-5x=19 | | -x-6=28 | | 5n^2+20n-25=0 | | 9a^2+15a-36=0 | | 5-4x-4x^2=0 | | 3(x-6)=3x+7 | | -5(2f-6)= | | 5(x-3)=x+12 | | 15=16+3x | | 3x^2=x(kx+8)+2 | | 12x^2-46x-36=0 | | 2v^2-1v+0=0 | | 5y-13y=-28-36 | | 5m^2-38m+48=0 | | 9=10 | | 81-x=-39 | | 4x-(3x-5)=2x+11 | | x-2.3=1.1 | | 2x-x=-5+3 | | a-12=36 | | 5+2x=3+x | | 8x-4+3x=7x+x-14 |